POPULATION AND FUNCTIONAL DIVERSITY OF PHOSPHATE SOLUBILIZING BACTERIA FROM APRICOT (PRUNUS ARMENIACA) OF MID AND HIGH REGIONS OF HIMACHAL PRADESH - GULERIA, SHIWANI; SHARMA, KRITIKA; WALIA, ABHISHEK; CHAUHAN, ANJALI; C. K. SHIRKOT (The Bioscan, 2014)
Phosphate solubilizing microorganisms play an important role in supplementing phosphorus to the plants by several mechanisms and thus benefit plant growth and development. In this study, isolation, screening and characterization of phosphate solubilizing bacteria (PSB) from different apricot growing sites of mid and high hill regions of Himachal Pradesh were carried out. A total of one hundered and eighty eight bacterial isolates were recovered from the rhizosphere soils of the apricot trees. The cells of all bacterial isolates were rod shaped, motile and gram positive in reaction. Seventy two P-solubilizing bacterial isolates were selected and further characterized for different plant growth promoting activities. Indole acetic acid production was detected in 59.72% isolates, siderophore synthesis in 48.61% isolates, hydrogen cyanide in 5.55% isolates and the per cent growth inhibition against Dematophora necatrix was detected in 65.28% PSBs. Overall, 9.60% of PSB isolates from RS and 8.10% from ER showed none of the PGPTs tested. The study on distribution of PGPT-possessing PSBs revealed that they are distributed more within rhizosphere soil than in endorhizosphere according to Shannon-Weaver diversity index. The most efficient strain AG1(3) was identified as Bacillus subtilis by 16S rDNA analysis. Results indicated that identification and characterization of soil PSBs for the effective plant growth-promotion broadens the spectrum of phosphate solubilizers available for field.